The Influence of Focus Marking on Pronoun Resolution in Dialogue Context - Blything, Liam P.; Järvikivi, Juhani; Toth, Abigail G.; Arnhold, Anja (Frontiers in Psychology, 2021)
Using visual world eye-tracking, we examined whether adults (N=58) and children (N=37; 3;1-6;3) use linguistic focusing devices to help resolve ambiguous pronouns. Participants listened to English dialogues about potential referents of an ambiguous pronoun he. Four conditions provided prosodic focus marking to the grammatical subject or to the object, which were either additionally it-clefted or not. A reference condition focused neither the subject nor object. Adult online data revealed that linguistic focusing via prosodic marking enhanced subject preference, and overrode it in the case of object focus, regardless of the presence of clefts. Children’s processing was also influenced by prosodic marking; however their performance across conditions showed some differences from adults, as well as a complex interaction with both their memory and language skills. Offline interpretations showed no effects of focus in either group, suggesting that while multiple cues are processed, subjecthood and first mention dominate the final interpretation in cases of conflict.